2014
DOI: 10.1186/scrt530
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells/multipotent stromal cells consume accumulated autophagosomes early in differentiation

Abstract: IntroductionBone marrow mesenchymal stem cells/multipotent stromal cells (MSCs) are recruited to sites of injury and subsequently support regeneration through differentiation or paracrine activity. During periods of stress such as wound site implant or differentiation, MSCs are subjected to a variety of stressors that might activate pathways to improve cell survival and generate energy. In this study, we monitored MSC autophagy in response to the process of differentiation.MethodsMSC autophagosome structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 35 publications
5
78
0
Order By: Relevance
“…Briefly, we found rapid uptake of glucose in MSC cultures, coinciding with a glycolytic MSC phenotype that suggests a key role for glucose in implant sites or approaches to extending MSC lifespan. We also found that MSC autophagy, which we have previously found is a unique and important process in MSC function [4], responded rapidly to changes in glucose concentration. Interestingly, in a separate series of experiments, oxygen deprivation did not increase autophagy, and our calculations suggested that only in near anoxic conditions (<1%) would this be rate limiting; thus, we did not isolate this nutrient in these in vitro manipulations.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Briefly, we found rapid uptake of glucose in MSC cultures, coinciding with a glycolytic MSC phenotype that suggests a key role for glucose in implant sites or approaches to extending MSC lifespan. We also found that MSC autophagy, which we have previously found is a unique and important process in MSC function [4], responded rapidly to changes in glucose concentration. Interestingly, in a separate series of experiments, oxygen deprivation did not increase autophagy, and our calculations suggested that only in near anoxic conditions (<1%) would this be rate limiting; thus, we did not isolate this nutrient in these in vitro manipulations.…”
Section: Introductionsupporting
confidence: 62%
“…We have previously found that MSC autophagy is intimately tied to normal MSC function in differentiation through a unique phenotype of accumulated autophagosomes in vitro [4]. This could explain how the cells survive the depletion of glucose, both in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data stand with a good agreement with Nuschke et al . who showed that human MSCs consume accumulated autophagosomes early in differentiation confirming autophagy key role in that process. Moreover, it was described that hypoxia‐mediated differentiation of RAW264.7 depends on autophagy activated via HIF‐1‐α .…”
Section: Discussionmentioning
confidence: 91%